Global Citizens, Language Issues, and Digital Economy: An In-quiry of Financial Technology Adoption among International Students - Sithu Moe; Amirul Mukminin; Lenny Marzulina; Kasinyo Harto; Dian Erlina; Rahmah Fithriani; Fridiyanto Fridiyanto; Muhamad Holandyah; Dairabi Kamil; Fatin Aliya Mohd Ali; Azzam Alshehari (International Journal of Engineering, Science and Information Technology, 2025)
Financial Technology (FinTech) has significantly changed the landscape of Indonesia’s digital economy. On the other hand, the increasing non-domestic population in Indonesia, especially the student age group, also reflects the broadening demographic dynamics. This group plays a crucial role as a consumer in national economic growth. Despite the increasing growth of the national digital economy, the non-domestic population, especially the student age group, is doubtful about the acceptance of using FinTech. This paper investigated non-domestic students’ intention to use FinTech in Indonesia. The authors employed mixed methodology with an explanatory sequential design. Thus, this paper explored this narrative based on the technology acceptance model (TAM) and external factors such as Performance Expectancy (PE) and Social Influence (SI). Using the partial least squares (PLS) approach, data from the 75 non-domestic students in Indonesia were analyzed. In addition, this paper also utilized in-depth interviews to gather further information from participants. The thematic analysis of the semi-structured interviews was conducted to explore the non-domestic students’ experience of using Indonesian FinTech.